The number of Barnacle Geese in Europe in 1959-60 - Boyd, Hugh (Wildfowl, 1961)
A co-operative international inquiry in the winter of 1959-1960 resulted in an estimate of about 30,000 for the world population of Branta leucopsis. At 1st December, 1959 there were about 11,100 in the Netherlands, 8,600 in Germany, 7,100 in Scotland and 2,800 in Eire. No other country is likely to have held more than a few stragglers at that date. Evidence from ringing and from observations on the proportions of first-winter birds in different flocks suggests that the geese in the Netherlands and Germany are those breeding in Novaya Zemlya and Vaigach Island, off the Siberian coast. Scottish birds include some from Spitzbergen, and more from east Greenland. The Irish geese probably come only from Greenland. The stocks from Siberia and Spitzbergen have apparently recovered in recent years from the dangerously low levels they reached in 1945-1950, although aerial surveys in Sweden show that numbers stopping there in spring have decreased greatly in the last few years. Barnacle geese breeding in Greenland are faring less well than the other two stocks.